The Rise of Non-State Actors in Globalization and Democratization Era: Terrorist Group versus State Actors - Aji Widiatmaja; Fajria Hasta Rizqi (Jurnal Sentris, 2019)
Globalization brings together both mobility upheaval and democratization in technology for every state, organization, and people around the world. These phenomena make information, technology, and networking which a long time ago become state domain are today accessible for everyone. It gives a leeway for non-state actors which used to be powerless can speak louder in present day. However, this likely rejoice phenomena sometimes produce another side effect. The leeway also gives relatively easy access for certain non-state actors to achieve power that in the same time endanger world order. These non-state actors are terrorist groups which today possess great power, energized by globalization and democratization of technology, to balance the power of states. They utilize globalization and democratization era to organize, create image, build network, fund, and disseminate their activities around the globe. This study aims to analyze the rise of terrorist groups threats in today globalization and democratization era and in the same time examine the declining of state roles in international stages. This study uses descriptive qualitative method and using Globalization, Soft Power, and Balance of Power theories to dissect and analyze those phenomena. Several recommendations will be drawn from the analysis to contribute in making a robust and comprehensive international cooperation to combat terrorist groups.